2022
DOI: 10.1093/hr/uhab022
|View full text |Cite
|
Sign up to set email alerts
|

TheChrysanthemum lavandulifoliumgenome and the molecular mechanism underlying diverse capitulum types

Abstract: Cultivated chrysanthemum (Chrysanthemum × morifolium Ramat.) is a beloved ornamental crop due to the diverse capitula types among varieties, but the molecular mechanism of capitulum development remains unclear. Here, we report a 2.60 Gb chromosome-scale reference genome of C. lavandulifolium, a wild Chrysanthemum species found in China, Korea and Japan. The evolutionary analysis of the genome revealed that only recent tandem duplications occurred in the C. lavandulifolium genome after the shared whole genome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 69 publications
3
42
0
Order By: Relevance
“…they were ultrafragmented. Such fragmentation was similarly observed in the de novo assemblies of diploid Chrysanthemum species genomes obtained at an early stage [ 20 , 44 ] because repetitive sequences occupied >68.6% of the whole genome in the genus Chrysanthemum [ 20 , 29 , 44 , 49 ]. In this study, the high ratio of repetitive sequences could be a major cause of the failure in assembling longer sequences in cultivated chrysanthemums.…”
Section: Discussionmentioning
confidence: 78%
“…they were ultrafragmented. Such fragmentation was similarly observed in the de novo assemblies of diploid Chrysanthemum species genomes obtained at an early stage [ 20 , 44 ] because repetitive sequences occupied >68.6% of the whole genome in the genus Chrysanthemum [ 20 , 29 , 44 , 49 ]. In this study, the high ratio of repetitive sequences could be a major cause of the failure in assembling longer sequences in cultivated chrysanthemums.…”
Section: Discussionmentioning
confidence: 78%
“…We wished to include as many orders as possible in our study, ideally with access to at least six genomes with high quality, preferably chromosome-level, assemblies, distributed among at least three different families. At the time of data collection, we could obtain suitable data from three fabid orders, Fagales [20][21][22][23][24][25][26][27], Cucurbitales [28][29][30][31][32][33], Malpighiales [34][35][36][37][38][39]; three malvid orders, Myrtales [40][41][42][43][44], Malvales [45][46][47][48][49][50] and Sapindales [51][52][53][54][55][56][57][58][59][60][61]; one campanulid order, Asterales [62][63][64][65][66]…”
Section: Resultsmentioning
confidence: 99%
“…In our study, intact CCD4a sequences were detected in the genomes of all chrysanthemums with white/pink ray florets and some Ajania species, but were absent in most Ajania and yellow‐rayed chrysanthemums (Table 2). The absence of CCD4a in genomes of Chrysanthemum species with yellow marginal florets was supported by the whole‐genome sequence data of C. nankingensis (Song et al ., 2018), C. seticuspe (Hirakawa et al ., 2019) and C. lavandulifolium (Wen et al ., 2022). Our analyses revealed that CCD4a was specifically expressed in the white rays of radiate capitula, in which CYC2g was functional, but it was not expressed in the marginal florets of disciform capitula, in which CYC2g was dysfunctional (Figs 2, 3).…”
Section: Discussionmentioning
confidence: 99%